Modern technologies of e-learning - G. A. gyzy Mamedova; F. T. ogly Agaev (Открытое образование (Москва), 2017)
E-learning constitutes a significant competition to traditional education in many countries and has become a major tool for the modernization of education and economic growth. For the development and implementation of successful e-learning systems, we need technologies that allow working with them for any number of users, providing a good learning environment. The article provides an overview of the technologies used in foreign universities for managing e-learning, such as 3D technologies in training programs, interactive technologies, personalization of learning using cloud computing and big data technologies. It is shown that today quite a large number of software and hardware development was created and introduced, implementing various mechanisms of introducing information technologies in the educational process. One of such developments is the use of adaptive technologies in the learning process, allowing the student to adapt to the training material, choose the suitable method of mastering the material, and adjust the intensity of training at different stages of the learning process. Another development of information technologies in education is the use of cloud computing, allowing access to educational resources for teachers, students, and managers of the education system. It was revealed that the use of cloud technologies leads to a significant decrease in material costs for the purchase of expensive equipment and software, educational content from the cloud can be accessed from any device (laptop, smartphone, tablet, etc.) and at a convenient time for the learner, it is enough to have Internet connection and a browser. In the e-learning environment, there are many different types of data, both structured and unstructured, processing of which is difficult to implement using traditional statistical methods. For the processing of such data technologies of processing big data are used such as NoSQL and Hadoop. The article shows that the analysis of big data makes it possible for teachers to receive information about students in due time, and allows them to customize the learning strategy. Using big data, teachers get a rare opportunity to monitor the whole process and identify how well students perform tasks, or how quickly they completed the challenging course modules. This will enable them to develop more personalized e-learning courses. The article gives examples of educational practice, illustrating the substantial change of the educational environment of the university involving the use of these technologies in e-learning. The results can be used to make recommendations for creating e-learning courses in higher and secondary educational institutions of Azerbaijan.